Inequity, poverty and health. (Colombia Medica, 2006)
One of the biggest barriers to reduce the poverty is the distributive inequity of the wealth. The Colombian society is poor, it presents an unequal distribution of the entrance and it grows a little. Fourteen million Colombians survive with less than two daily dollars. In total, 64 of each 100 Colombians are in the «threshold» of poverty. If Colombia wants to have prosperity and social justice, is requires to assist the justness among its rural and urban areas, among its regions, among ethnic groups and between men and women in aspects like the access to the education, the property of the earth and the distribution of income. The economic growth not only requires healthy individuals, but also education and other complementary investments, an appropriate division of the work among the public sectors and private, a good operation of the markets, an appropriate public administration and institutional agreements that impel the technological advances. New studies suggest that the stress of being poor has a dangerous influence in the health. People of socioeconomic stratum low they have dramatically more risk of making sick and expectation of shorter life. There is a strong association among inequity in the revenues, poor health and low capital stock. A high inequity grade in the revenues takes to a confidential low-level and support, that which increases the stress and dangers for the health. An immense responsibility of the rich countries exists in the execution of the goals of reduction of the poverty and improvement of the conditions of life in the world. Most of the deaths are avoidable and it is necessary to approach the structural causes of the poverty and the inequality. There are capacity and enough resources in the world to eradicate the hunger and the poverty and to promote the sustainable economic development with social justice.